KEWENANGAN KOMISI PENYIARAN INDONESIA (KPI) DALAM MENGAWASI SIARAN KAMPANYE PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN 2014 - Muhriani, Nelly (Katalogis, 2015)
The purposes of this research are to examine and analyze the implementation of The Indonesian Broadcasting Commission’s authority in monitoring the campaign broadcast of the presidential election in 2014, as well as to find out the effectiveness of sanctions for violations of campaign broadcast of the Presidential election in 2014. The method of the research is empirical juridical through data collection techniques are primary and secondary data. The conclusions can be drawn are (1) The authority of The Indonesian Broadcasting Commission, in carrying out monitoring function of The Campaign Broadcast of The Presidential Election in 2014 have been reduced and deliberately weakened by The government, indicated with several times of judicial review of The Broadcasting Act, in particular matters related with the authority of The Indonesian Broadcasting Commission in monitoring the broadcast campaign. (2) In imposing sanctions, The Indonesian Broadcasting Commission is only allowed to give a written warning or to reduce the duration of the program rather than the revocation of the broadcast. Although, the violations had crossed the line, The Indonesian Broadcasting Commission is only entitled to provide recommendation to The Ministry of Communication and Information to evaluate the license of broadcasters, whether extended or revoked. Therefore, researcher suggests such things : (1) The role and authority of The Indonesian Broadcasting Commission must be further strengthened by The Act No. 32 Year 2002 on broadcasting, concerning about strict sanctions to broadcasters who violate The Campaign Broadcast of the next Presidential Election in 2019. (2) The government must revise and confirm the regulation about the practice of conglomeration and monopoly of broadcasting enterprise in Indonesia so that objectivity can be maintained in accordance with the order of the national broadcasting as contained in Pancasila and The 1945 Constitution.